2018
DOI: 10.1002/hep4.1138
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus replication and interferon responses in human placental cells

Abstract: Hepatitis E virus (HEV) is a member of the genus Orthohepevirus in the family Hepeviridae and the causative agent of hepatitis E in humans. HEV is a major health problem in developing countries, causing mortality rates up to 25% in pregnant women. However, these cases are mainly reported for HEV genotype (gt)1, while gt3 infections are usually associated with subclinical courses of disease. The pathogenic mechanisms of adverse maternal and fetal outcome during pregnancy in HEV‐infected pregnant women remain el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 53 publications
2
38
1
Order By: Relevance
“…In this study, we showed that HEV RNA and HEV ORF2 Ag were increased over time in PHESCs challenged with HEV preparations, indicating efficient replication in vitro and the life cycle of HEV is completed in these cells. Similar kinetic in HEV RNA and capsid proteins were reported in other cell lines that support HEV replication and represent sites of extrahepatic HEV replication, such as neuron and placenta-derived cell lines [36,37]. HEV-1 replicates more efficiently in PHESCs than HEV-3.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we showed that HEV RNA and HEV ORF2 Ag were increased over time in PHESCs challenged with HEV preparations, indicating efficient replication in vitro and the life cycle of HEV is completed in these cells. Similar kinetic in HEV RNA and capsid proteins were reported in other cell lines that support HEV replication and represent sites of extrahepatic HEV replication, such as neuron and placenta-derived cell lines [36,37]. HEV-1 replicates more efficiently in PHESCs than HEV-3.…”
Section: Discussionsupporting
confidence: 76%
“…PHESCs were treated with 50 µM of RBV (Sigma-Aldrich, Darmstadt, Germany) after HEV infection as described previously [29,36,37] with a slight modifications in the procedure. Briefly, 2 × 10 4 cells/well were seeded in a 24-well plate and were incubated at 37 • C. After 24 h, culture medium was removed, and the cells were challenged with HEV preparations (10 6 IU/mL) with or without RBV.…”
Section: Testing the Effect Of Ribavirin (Rbv) On Hev Replication In mentioning
confidence: 99%
“…The 3= UTR of HEV induced predominantly type I IFN responses in enterocytes. A tissue-specific IFN response has been reported during HEV infection (23,24). Therefore, in addition to liver tissues from HEV-infected pigs and Huh7-S10-3 liver cells, we also determined the IFN mRNA expression levels in HEV SL1-and SL3-stimulated swine enterocyte IPEC-J2 cells using gene-specific RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that HEV induced IFN in both host cell-dependent and genotype-specific manners (23,24). Therefore, in this study, we tested the IFN induction ability by HEV RNA PAMPs in both hepatocytes and enterocytes, since the primary site of HEV replication is the small intestine before reaching the target organ (the liver).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation